2021
DOI: 10.1111/ijtd.12255
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of accountability for the transfer of training by leadership trainers

Abstract: Schlenker’s model of responsibility was used in this study to investigate to what extent leadership trainers consider themselves accountable for the transfer of training. We conducted 15 semi‐structured interviews and evaluated the answers using qualitative content analysis. With respect to the responsibility links of Schlenker’s model, the trainers described two out of three links as being rather strong. The interview data suggest that transfer‐enhancing strategies were mostly clear to the trainers. They also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…TMR has mainly been used to identify the antecedents of responsibility judgment in professional contexts, such as investors' management responsibility for an adverse event (Tan & Yu, 2018), auditors' professional responsibility for detecting fraud (DeZoort & Harrison, 2018), and trainers' responsibility for training (Wisshak & Barth, 2021). Although Schlenker et al (1994) demonstrated the potential of using TMR to explain individuals' responsibility in personal contexts, such as parents' responsibility for school chaperoning and students' responsibility for class performance, little research has used TMR to examine responsibility in interpersonal interactions, especially for online contexts.…”
Section: Antecedents Of Responsibilitymentioning
confidence: 99%
“…TMR has mainly been used to identify the antecedents of responsibility judgment in professional contexts, such as investors' management responsibility for an adverse event (Tan & Yu, 2018), auditors' professional responsibility for detecting fraud (DeZoort & Harrison, 2018), and trainers' responsibility for training (Wisshak & Barth, 2021). Although Schlenker et al (1994) demonstrated the potential of using TMR to explain individuals' responsibility in personal contexts, such as parents' responsibility for school chaperoning and students' responsibility for class performance, little research has used TMR to examine responsibility in interpersonal interactions, especially for online contexts.…”
Section: Antecedents Of Responsibilitymentioning
confidence: 99%